Feldspar Solid Solution Series in Fenites from Loe Shilman Carbonatite Complex NW Pakistan - Mian1, Ihsanullah; Le Bas, M.J. (Journal of Himalayan Earth Sciences, 1988)
The carbonatite sheets at Loe Shilman in Khyber Agency, NW Pakistan, fenitize their country rocks to form a metasomatic zone, c. 100 metres wide, of alternate dark blue (mafic) and pale grey (felsic) banded fenites which grade into unfenitized slates and phyllites. The carbonatite sheets comprise a more extensive amphibole sovite which is intruded by biotite sovite in different parts of the complex. These sovites are in turn intruded by ankeritic carbonatite mainly along the southern contact with the country rocks. Amongst the new minerals, formed as a result of three fenitizations (two sodic and one potassic), K-feldspars are formed as a result of contact thermal effect by the early amphibole sovite at the expense of phengite and argillaceous material. The more disordered K-feldspars, which were formed at high temperature ("700˚C), in the inner zones 3, 4 and 5, are now readjusted to maximum-microcline to intermediate- microcline. While in zone 2 the more disordered relict K-feldspar escaped readjustment, and therefore, produces reverse zonation in contrast to the temperature gradient. The effect of biotite sovite is restricted to the thin veins composed of K-feldspar (Ba=1.4 wt %) and biotite. The samples SM93 and SM84, amongst the banded fenites, have been also metasomatized by the biotite sovite. Albite, which coexists with other metasomatic minerals, formed first by the early amphibole sovite, was presumably more disordered towards the carbonatite contact. It is now readjusted to its present lowest structural state by the ankeritic carbonatite. The presence of relict disordered intermediate low-albite now shows reverse zonation in contrast to the temperature gradient. Both the solid solution series are well correlated with distance from the carbonatite igneous contact.